Extensions of Extension: Socialization and Credibility Constraints On Private Crop Production Advisors - Gerry Walters (Journal of Applied Communications, 1991)
A study of private crop production information sources finds the analytical frameworks underlying their recommendations to clients are much narrower than the available range of analyses.